Temperate deciduous shrub and tree in situ spring phenology 2023 - 2025 - Donnelly, Alison (PANGAEA, 2025)
This data set includes in situ phenological observations (Day of year) for a range of spring phenophases (budburst, leaf-out and full leaf unfolded) (2017-2021) for co-occurring species of tree Tilia americana (American-basswood), Quercus rubra (red-oak), Quercus alba (white-oak) and Acer negundo (boxelder)) and shrub (Native species: Prunus virginiana (chokecherry), Cornus alternifolia (pagoda-dogwood), Viburnum lentago (nannyberry), Ribes americanum (American-wild-currant) and Euonymus atropurpureus (Eastern wahoo) and Non-native species: Rhamnus cathartica (buckthorn), Lonicera morrowii (honeysuckle), Ligustrum vulgare (European-privet) and Viburnum opulus (European-highbush-cranberry)) in an urban woodland fragment in Wisconsin, USA. Spring data span 2023 - 2025. Note: these data are a continuation of data included in Donnelly et al., 2024. This updated data set does not include observations for Fraxinus spp. (Ash) as it has been removed from the study site due to the invasive beetle the Emerald Ash Borer.
Keywords: budburst; full-leaf out; leaf-out; native and non-native shrubs; phenology; spring; temperate deciduous shrubs; temperate deciduous trees